Single-layer Laguerre neural network model for solving Lane-Emden-Fowler type equations - Kurmanc, Sena Nur; Ozavsar, Muttalip (UNIV OSIJEK, DEPT MATHEMATICS, 2025)
In this study, a single-layer functional link artificial neural network (FLANN) model based on Laguerre polynomials, referred to as the Laguerre Neural Network (LgNN), is utilized to solve second-order linear and non-linear equations of Lane-Emden-Fowler type. Using this model, in which the hidden layers are replaced with Laguerre polynomials, we initially expand the input patterns corresponding to a given set of nonlinear Lane-Emden-Fowler type equations. Subsequently, the network parameters are adjusted through an unsupervised error backpropagation algorithm that employs Adam optimization. Consequently, we compare the LgNN results with those obtained by other FLANNbased models, namely the Chebyshev Neural Network (ChNN) and the Legendre Neural Network (LeNN), by solving some initial value problems of Lane-Emden-Fowler type equations.
Keywords: Lane-Emden-Fowler equation; single-layer functional link artificial neural network; Laguerre neural network; Chebyshev neural network; Legendre neural network; Adam Optimization; NUMERICAL-SOLUTION; DECOMPOSITION METHOD; IVPS; Mathematics